Cost−utility analysis of shockwave lithotripsy vs ureteroscopic stone treatment in adults. (16th August 2022) - Kilonzo, Mary M.; Dasgupta, Ranan; Thomas, Ruth; Aucott, Lorna; MacLennan, Sara; Lam, Thomas Boon L.; Anson, Ken; Cameron, Sarah; Starr, Kath; Burgess, Neil; Keeley, Francis Xavier; Clark, Charles T.; et al.
Abstract : Objectives: To assess the cost‐effectiveness, resource use implications, quality‐adjusted life‐years (QALYs) and cost per QALY of care pathways starting with either extracorporeal shockwave lithotripsy (SWL) or with ureteroscopic retrieval (ureteroscopy [URS]) for the management of ureteric stones. Patients and Methods: Data on quality of life and resource use for 613 patients, collected prospectively in the Therapeutic Interventions for Stones of the Ureter (TISU) randomized controlled trial (ISRCTN 92289221), were used to assess the cost‐effectiveness of two care pathways, SWL and URS. A health provider (UK National Health Service) perspective was adopted to estimate the costs of the interventions and subsequent resource use. Quality‐of‐life data were calculated using a generic instrument, the EuroQol EQ‐5D‐3L. Results are expressed as incremental cost‐effectiveness ratios and cost‐effectiveness acceptability curves. Results: The mean QALY difference (SWL vs URS) was −0.021 (95% confidence interval [CI] −0.033 to −0.010) and the mean cost difference was −£809 (95% CI −£1061 to −£551). The QALY difference translated into approximately 10 more healthy days over the 6‐month period for the patients on the URS care pathway. The probabaility that SWL is cost‐effective is 79% at a society's willingness to pay (WTP) threshold for 1 QALY of £30, 000 and 98% at a WTP threshold of £20, 000. Conclusion: The SWL pathway results in lower QALYs than URS but costs less. The incremental cost per QALY is £39 118 cost saving per QALY lost, with a 79% probability that SWL would be considered cost‐effective at a WTP threshold for 1 QALY of £30 000 and 98% at a WTP threshold of £20 000. Decision‐makers need to determine if costs saved justify the loss in QALYs.